Analysis of Economic Sector Potential in East Kutai District - Ibnu Khaldun; Rahcmad Budi Suharto; Juliansyah Roy (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
The aim of this research is to identify and analyze the economic potential of the base sector so that economic growth in East Kutai Regency can increase. Classification of economic sectors that have advantages and potential and can be developed to boost economic growth in East Kutai Regency. An overview of the pattern and structure of economic growth in East Kutai Regency. This research uses quantitative secondary data. The approach used is the Location Quotient (LQ) analysis tool to identify economic sectors that are the base sectors, Shift Share analysis to identify economic sectors that have the potential to become leading sectors and Klassen Typology analysis to identify a picture of the pattern and structure of economic growth to support economic development and regional development in East Kutai Regency. The research results show that during the research period, namely from 2013 to 2022, the mining and quarrying sector still dominates the economic structure of East Kutai Regency with the contribution of this sector to the total GRDP of 83.37%. The Mining and Quarrying sector in East Kutai Regency is a basic sector, so changes in GRDP growth or policy changes in the mining and quarrying sector are believed to have an impact on the formation of GRDP as a whole and besides that, this sector also has competitive advantages and is included in the fast-growing sector. and grow fast. East Kutai Regency in 2013-2022 shows that there are eight economic sectors that have a negative sign (PPij < 0) or slow growth, namely the Agriculture, Forestry and Fisheries sectors amounting to Rp. – 53,630.94,-, Processing Industry sector Rp. – 117,477.84,-, Transportation and Warehousing sector Rp. – 24,119.22,-, Financial Services sector Rp. – 2,233.09, Real Estate sector Rp. – 10,176.60, Corporate Services sector Rp. – 1,288.94, Government Administration, Land and Mandatory Social Security sectors amounting to Rp. – 4,012.91, Education Services sector Rp. – 7,759.64,-. This happens because at the provincial level the growth of these sectors has slowed down, resulting in a slow growth impact on the same sectors in East Kutai Regency.